Habermas and the issue of religion in the public space:critical contributions to a new view on State laicity - Lucas de Jesus Correia, Raique; Gama, Marta; Busanello Ferreira, Fernanda (Revista da Faculdade de Direito do Sul de Minas, 2021)
Modernity has inaugurated a new stage in the relationship between ecclesiastical and secular power. On the one hand, the extinction of religions was thought of as an inevitable future; on the other, the emergence of religious orthodoxies on a global scale brought to light the complexity of a new political arrangement, in which religious and non-religious citizens vie for the establishment of their agendas. At a time when secularized societies experience the religious revival in the public sphere, the concept of “secularism” takes on new shapes and can no longer mean a simple movement to combat religious presence in these spaces or a mere institutional arrangement of separation between State and Church. In this article we seek to investigate to what extent Habermas’ proposal that religion can no longer be fought as an evil to be expelled and imprisoned in the intimate sphere of individuals, and must adapt its presence in the public space through legitimate contributions to the deliberative process, constitutes an adequate model to the Brazilian reality, verifying its limits and possibilities. In view of the above, the present article intends to examine the Habermasian model of “post-secular state” as an alternative to the current model based on laicism, through bibliographic research and using the hypothetical-deductive method. To this end, we propose a review of the main concepts formulated by Habermas, from the publication of the “Theory of Communicative Action” to the most recent texts and essays. In addition, it will also seek to answer some criticisms and formulate other questions, to delimit the viability of the Habermasian paradigm, above all, considering the Brazilian reality. In this sense, we present an outline of the arguments raised by Habermas in defense of religious participation in the public space and the parameters endorsed by him as a way of guaranteeing state neutrality. Finally, we confront his theses with the position of Brazilian authors and conclude by recognizing some weaknesses in his theoretical model, stressing, however, the importance of his contributions to the composition of a plural public space and a democracy attentive to the voices of all citizens.